The correlation between proprotein convertase subtilisin/kexin type 9 and adiponectin in the progression from prediabetes to type 2 diabetes mellitus - Jun-Xu Gu; Kun Wang; Ai-Min Zhang; Yue Yin; Shan-Shan Li; Na Zhang; Li Qin; Chun-Yan Wang; Lin Pei; Mei Jia; Ming Su (Scientific Reports)
Abstract Data on the involvement of proprotein convertase subtilisin/kexin type 9 (PCSK9) and adiponectin in prediabetes progression to type 2 diabetes mellitus (T2DM) remains inconclusive. Therefore, this study investigated the roles of PCSK9 and adiponectin in this process. This study included 1,528 participants with prediabetes and T2DM and conducted correlation analyses to investigate the relationship between PCSK9 and adiponectin levels, pancreatic beta-cell function, and insulin levels. Logistic regression analysis and receiver operating characteristic (ROC) curves were used to determine whether PCSK9 and adiponectin play protective roles in the progression from prediabetes to T2DM and their potential as diagnostic biomarkers for T2DM. In prediabetic patients, the levels of PCSK9 [573.00 (412.35) ng/mL vs. 924.20 (673.38) ng/mL, p < 0.001] and adiponectin [4.50 (2.80) mg/mL vs. 6.22 (4.51) mg/mL, p < 0.001] were significantly higher than those in patients with T2DM. PCSK9 (r = 0.167, p < 0.001) and adiponectin (r = 0.113, p < 0.001) levels were positively correlated with pancreatic cell homeostasis and had protective effects against progression from prediabetes to T2DM (PCSK9: OR = 0.274, 95% CI 0.121–0.621, p = 0.002; adiponectin: OR = 0.135, 95% CI 0.057–0.320, p < 0.001). The combined diagnostic value of PCSK9 and adiponectin for T2DM showed an area under the curve of 0.751 (95% CI 0.727–0.775). Prediabetes and T2DM patients showed significant differences in the PCSK9 and adiponectin levels. PCSK9 and adiponectin have protective effects against the progression of prediabetes to T2DM, and their combined use is a potential biomarker for the transition from prediabetes to T2DM.